2015
DOI: 10.1128/aac.04618-14
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling of Plasma and Intracellular Ribavirin Concentrations in Patients with Chronic Hepatitis C Virus Infection

Abstract: e Ribavirin, a guanosine analog, is a broad-spectrum antiviral agent. Ribavirin has been a fundamental component of the treatment of hepatitis C virus (HCV) infection for decades, but there is a very limited understanding of the clinical pharmacology of this drug. Furthermore, it is associated with a major dose-limiting toxicity, hemolytic anemia. Ribavirin undergoes intracellular phosphorylation by host enzymes to ribavirin monophosphate (RMP), ribavirin diphosphate (RDP), and ribavirin triphosphate (RTP). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…This analysis showed that ribavirin coadministration did not affect the pharmacokinetics of any of the DAAs in HCV genotype 1‐infected subjects, as ribavirin was not identified as a covariate in any of the analyses. Ribavirin values of clearance and volume parameters estimated from the population pharmacokinetic analysis were in close agreement with those reported in the population pharmacokinetic analysis of phase Ib and II studies of the 3D regimen and in the literature , suggesting that the pharmacokinetics of ribavirin were not altered when coadministered with the 3D regimen. The weight‐based ribavirin dosing used in the clinical trials that contributed to the present analysis provided consistent exposures across the various covariates.…”
Section: Discussionsupporting
confidence: 84%
“…This analysis showed that ribavirin coadministration did not affect the pharmacokinetics of any of the DAAs in HCV genotype 1‐infected subjects, as ribavirin was not identified as a covariate in any of the analyses. Ribavirin values of clearance and volume parameters estimated from the population pharmacokinetic analysis were in close agreement with those reported in the population pharmacokinetic analysis of phase Ib and II studies of the 3D regimen and in the literature , suggesting that the pharmacokinetics of ribavirin were not altered when coadministered with the 3D regimen. The weight‐based ribavirin dosing used in the clinical trials that contributed to the present analysis provided consistent exposures across the various covariates.…”
Section: Discussionsupporting
confidence: 84%
“…As such, there is less need for high concentrations of these molecules and so the quantities are lower compared to PBMCs. Additionally, the MP is the rate limiting step to become the TP, and higher TP is favored when nucleotide pools are at equilibrium (23, 30). The exception to this would be IMP in PBMCs since it is an important molecule for the production of other nucleotides via the de novo synthesis pathway in nucleated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical samples (PBMCs, RBCs and DBS) were obtained from 36 hepatitis C-infected individuals participating in an IRB-approved study of ribavirin (RBV) pharmacokinetics (23). All patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…We had previously identified higher RBV‐TP concentrations in individuals with variant ITPA phenotypes in 2 smaller studies but wished to confirm this association in a larger cohort of patients with a greater number of individuals with variant ITPA phenotypes. Studying a larger population allowed for an analysis of 4 different ITPA activity phenotype groups (ie, 100%, 60%, 30%, and ≤10%) rather than simply 100% activity vs less than 100% activity.…”
Section: Discussionmentioning
confidence: 96%
“…However, ITPA‐deficient individuals appear to have a similar rate of SVR as nondeficient individuals despite this potential decrease in RBV‐TP . There are limited data on the association between ITPA genetics and RBV pharmacokinetics . Because RBV is an analogue for adenosine and guanosine and is phosphorylated to active RBV‐TP in the cell, it is likely that ITPA activity will have an effect on its intracellular pharmacology.…”
Section: Itpa Genotype Groups With Number and Percentage Of Patients mentioning
confidence: 99%